A kind of vermiculite nanosheet composite film and preparation method thereof
The traditional vermiculite film production is solved by introducing vermiculite nanosheets, carbon nanotubes and rare earth metal oxide nanosalts into the vermiculite film and forming a composite layer with polymer electrolytes, polyhydroxy organic acids and water-absorbing inorganic salts. The problem of complexity and functionality is single, and a vermiculite nanosheet composite film with high stability and high ion migration rate is achieved.
Patent Information
- Application Number
- CN202410463491.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-04-17
AI Technical Summary
Traditional vermiculite film production has problems such as low conversion rate of raw materials, complex processes, relatively single functionality and narrow application scope.
Vermiculite nanosheets, carbon nanotubes and rare earth metal oxide nanosalts are used to form a functional layer, and a composite layer is formed with polymer electrolytes, polyhydroxy organic acids and water-absorbing inorganic salts. Through simple structural design and preparation methods, a composite layer is formed. Vermiculite nanosheet composite film.
It improves the stability and ion migration rate of the film, enhances the inlet and outflow rate of molecules in the film, reduces the preparation cost and difficulty, and expands the scope of application.
Smart Images

Figure CN118320642B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional films and relates to a vermiculite nanosheet composite film and a preparation method thereof. Background Art
[0002] There are several problems with traditional vermiculite membrane production:
[0003] (1) The raw material conversion rate is low and the raw material input is large;
[0004] (2) The process is complicated, requiring repeated adjustment of pH, introducing organic solvents, and some processes require high temperature and high pressure;
[0005] (3) The functionality is relatively simple and the scope of application is narrow.
[0006] Patent CN110449037A discloses a two-dimensional layered vermiculite film, preparation and application, including the following steps: Step 1: Mixing heat-expanded vermiculite with a water-absorbing inorganic salt solution, heating and stirring, centrifugal washing, and obtaining powder A; Step 2: Mixing powder A with hydrogen peroxide, heating and stirring, centrifugal washing, and obtaining powder B; Step 3: Mixing powder B with water, stirring at room temperature, centrifuging at high speed to remove impurities, and centrifuging at low speed to obtain a high-concentration, large-size two-dimensional vermiculite nanosheet solution; Step 4: Stacking the two-dimensional vermiculite nanosheets obtained in step 3 on the surface of a porous substrate in layers to obtain a two-dimensional layered vermiculite film. However, the preparation process of this patent is complicated to operate and has a low output rate; the produced film is relatively fragile and easy to damage. Summary of the invention
[0007] The purpose of the present invention is to provide a vermiculite nanosheet composite film and a preparation method thereof in order to overcome at least one defect of the above-mentioned prior art. The present invention has higher stability and ion migration rate, thereby improving the rate of entry and exit of molecules in the film.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] One of the technical solutions of the present invention is to provide a vermiculite nanosheet composite film, which includes a functional layer and a composite layer, wherein the functional layer includes vermiculite nanosheets, carbon nanotubes and rare earth metal oxide nano-slurry, and the composite layer includes a polymer electrolyte, a polyhydroxy organic acid and a water-absorbing inorganic salt.
[0010] Furthermore, the carbon nanotubes are selected from one or more of hydroxylated carbon nanotubes and plasma surface treated carbon nanotubes, and the rare earth metal in the rare earth metal oxide nanoslurry is selected from one or more of cerium, neodymium, thorium, yttrium and lanthanum.
[0011] As a preferred technical solution, the carbon nanotubes are hydrophilic carbon nanotubes, and the rare earth metal oxide nano-slurry is water-based rare earth metal oxide nano-slurry.
[0012] As a preferred technical solution, the particle size of the carbon nanotubes is 0.1-0.6 μm.
[0013] Furthermore, the polymer electrolyte is selected from one or more of polyvinyl alcohol (PVA), polydiallyldimethylammonium chloride (PDDA), polyethylene (PE), polyamide (PA), and polystyrene sulfonic acid (PSS); the polyhydroxy organic acid is selected from one or more of phytic acid, tannic acid, and gallic acid; and the water-absorbing inorganic salt is selected from one or more of lithium chloride, magnesium chloride, and calcium chloride.
[0014] As a preferred technical solution, the polyhydroxy organic acid can also be replaced by various types of polycarboxyl organic acids or sulfonic acids.
[0015] Furthermore, the thickness ratio of the functional layer to the composite layer is (1-10):(2-30).
[0016] As a preferred technical solution, the thickness of the functional layer is 10-100 μm, and the thickness of the composite layer is 20-300 μm.
[0017] As a preferred technical solution, the film is supported on a support.
[0018] As a preferred technical solution, the support is selected from one or more of polyethylene terephthalate (PET), polyethylene, and polyvinyl chloride (PVC).
[0019] As a preferred technical solution, the support may also be replaced by various stable non-metallic substances.
[0020] One of the technical solutions of the present invention is to provide a method for preparing the vermiculite nanosheet composite film, which comprises the following steps:
[0021] S1, dispersing vermiculite in water to form a vermiculite nanosheet suspension, adding carbon nanotubes to the suspension and mixing them evenly with ultrasound, then adding rare earth metal oxide nano slurry to the suspension and mixing evenly to form a functional liquid, filtering the functional liquid and drying it to obtain a functional layer;
[0022] S2. Dissolve the polymer electrolyte and the polyhydroxy organic acid in water to form solutions and then mix them. Add a water-absorbing inorganic salt to the mixed solution and mix them evenly to form a composite liquid. Apply the composite liquid droplets on the functional layer and dry them to form a composite layer on the functional layer, thereby obtaining a vermiculite nanosheet composite film.
[0023] Furthermore, in step S1, the mass concentration of the vermiculite nanosheet suspension is 1-20 g / L, the mass fraction of carbon nanotubes relative to vermiculite is 0.1-5 wt %, the mass fraction of rare earth metal oxide nanoslurry relative to vermiculite is 0.3-10 wt %, and the volume / thickness ratio of the functional liquid to the functional layer is (1-3 mL):(1-10 μm).
[0024] Further, in step S1, the temperature of vermiculite dispersion is 20-35°C, the ultrasonic frequency is 15-35kHz, the output power is 500-2000W, and the time is 8-16h / 10g vermiculite;
[0025] The temperature of carbon nanotube ultrasound is 20-35°C, the frequency is 15-25kHz, and the time is 1-3h;
[0026] The temperature of the rare earth metal oxide nano-slurry mixing is 20-35°C, the stirring rate is 200-500rpm, and the time is 20-60min;
[0027] The functional liquid is dried at a temperature of 30-80°C and for 3-5 hours.
[0028] Furthermore, in step S2, the mass fraction of the polymer electrolyte solution is 10-30wt%, the mass fraction of the polyhydroxy organic acid solution is 15-35wt%, the volume ratio of the polyhydroxy organic acid solution to the polymer electrolyte solution is 1:(1-5), the mass fraction of the water-absorbing inorganic salt relative to the sum of the polymer electrolyte solution and the polyhydroxy organic acid solution is 2-10wt%, and the volume / thickness ratio of the composite liquid to the composite layer is (1-10mL):(2-30μm).
[0029] Further, in step S2, the temperature for dissolving the polymer electrolyte is 60-120° C., the stirring rate is 400-800 rpm, and the time is 1-2 h;
[0030] The temperature for dissolving the polyhydroxy organic acid is 20-35°C, the stirring rate is 200-500 rpm, and the time is 20-60 min;
[0031] The water-absorbing inorganic salt is mixed at a temperature of 20-35°C, a stirring rate of 200-500 rpm, and a time of 20-60 min;
[0032] The temperature of the composite liquid drying is 50-100°C and the time is 2-3h.
[0033] Furthermore, the method for loading the film on a support comprises the following steps:
[0034] Water is dripped onto the support, the film is covered on the support, and the loading is completed after the water evaporates.
[0035] The present invention uses vermiculite nanosheets as the functional layer: vermiculite nanosheets have good hydrophilicity and ionic conductivity, which can effectively guide the migration of water vapor, and its stable structural characteristics also ensure the stability of the material. Adding carbon nanotubes and rare earth metal oxide nano-slurry to vermiculite nanosheets can fill microscopic gaps, increase stability, and reduce overall resistance.
[0036] The present invention uses polymer electrolyte as the composite layer: the polymer electrolyte has good hygroscopicity and ionic conductivity, and can effectively absorb water vapor in the environment. By adding polyhydroxy organic acid, hygroscopic inorganic salt, etc., the speed of moisture absorption and release, as well as the speed of ion migration can be greatly increased.
[0037] The present invention adopts a simple structural design and preparation method: the present invention includes a functional layer and a composite layer, has a simple structure, and a relatively simple preparation method, which can increase the yield over a large area while reducing the cost. This simple structural design and preparation method makes the vermiculite film composite material easier to realize and optimize, has broad application prospects, and is expected to play an important role in various fields.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) Low cost: The vermiculite used in the present invention is a natural mineral with abundant resources and low price;
[0040] (2) Simple preparation method: The preparation method of the present invention is simple, which reduces the difficulty of preparation and is conducive to large-scale production;
[0041] (3) High water vapor ion exchange rate: The functional layer of the present invention uses vermiculite nanosheets, which have a large specific surface area. The added polyhydroxy organic acid, water-absorbing inorganic salt, etc. can effectively absorb moisture, thereby improving the water and ion migration efficiency;
[0042] (4) Good stability and durability: Since vermiculite nanosheets and carbon nanotubes have good stability and durability, the performance of the present invention will not be significantly reduced after long-term use, and the service life is longer. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the structure of the vermiculite nanosheet composite film in an embodiment of the present invention.
[0044] Description of the markings in the figure:
[0045] 1—functional layer, 2—composite layer, 3—support. DETAILED DESCRIPTION
[0046] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0047] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0048] Example:
[0049] A vermiculite nanosheet composite film and a preparation method thereof, the specific steps are as follows:
[0050] S1. Disperse 10 g of vermiculite solid in 2 L of deionized water, and ultrasonically treat at 20 kHz and 1000 W for 12 h at 25 ° C. Take the upper solution, evaporate the water, and concentrate to form a vermiculite nanosheet suspension with a mass concentration of 10 g / L; add hydrophilic hydroxylated modified carbon nanotubes with a mass fraction of 3 wt% and a particle size of 0.3 μm relative to the vermiculite to the suspension, and ultrasonically treat at 20 kHz for 2 h at 25 ° C. and mix well; then add aqueous cerium oxide nanoslurry (obtained by nano-grinding) with a mass fraction of 5 wt% relative to the vermiculite to the suspension, stir at 400 rpm for 30 min at 25 ° C. and mix well to form a functional liquid; take 20 mL of the functional liquid, filter the functional liquid, and dry it at 60 ° C. for 4 h. After drying, remove it from the filter paper to obtain a 40 μm functional layer 1;
[0051] S2, dissolving polyvinyl alcohol (PVA) in deionized water, stirring at 600 rpm for 1 h at 90°C to form a clear PVA solution with a mass fraction of 15 wt%, dissolving phytic acid in deionized water, stirring at 400 rpm for 30 min at 25°C to form a phytic acid solution with a mass fraction of 25 wt%, adding the phytic acid solution to the PVA solution at a volume ratio of 1:2, adding lithium chloride with a mass fraction of 5 wt% relative to the sum of the PVA solution and the phytic acid solution, stirring at 400 rpm for 30 min at 25°C to mix evenly to form a composite solution; taking 40 mL of the composite solution, applying the composite solution dropwise on the functional layer 1, and drying at 80°C for 2 h to form a composite layer 2 with a thickness of 160 μm on the functional layer, that is, obtaining a vermiculite nanosheet composite film;
[0052] S3. If the film needs to be loaded on a polyvinyl chloride (PVC) support 3, add a drop of deionized water to the support 3, cover the film on the support 3, and complete the loading after the water evaporates. Figure 1 shown.
[0053] Comparative Example 1:
[0054] PVC film.
[0055] The water vapor ion exchange rate test of the above film is carried out, and the specific steps are as follows:
[0056] Use a beaker to accurately weigh 300 mL of deionized water and place it all in the beaker;
[0057] The cup mouth was covered with a vermiculite nanosheet composite film with the same area as the cup mouth as the experimental group, and the open beaker was the control group;
[0058] Place the beaker in a constant temperature and humidity chamber, set the temperature to 30°C (±0.1°C) and the humidity to 30% (±1%);
[0059] After standing for 12 h, calculate the remaining volume of deionized water.
[0060] Under the experimental conditions of 30°C and 30% humidity, the residual water volume of the experimental group (vermiculite nanosheet composite film in the embodiment) was 111.1 mL, and the residual water volume of the control group was 124.4 mL. The water evaporation rate of the vermiculite nanosheet composite film was 108% of that of the open film, and the vermiculite nanosheet composite film maintained a similar and slightly better water vapor permeability than the open film. The same batch of experiments were compared with the PVC film in Comparative Example 1. The residual water volume of Comparative Example 1 was 171.0 mL, and the water evaporation rate of the vermiculite nanosheet composite film was 146% of that of the PVC film, proving that the vermiculite nanosheet composite film has increased the water vapor permeability compared with ordinary films such as PVC film.
[0061] Comparative Example 2:
[0062] Single layer vermiculite membrane.
[0063] The above films were subjected to resistance tests.
[0064] Using a multimeter to measure, the single-layer vermiculite film in Comparative Example 2 is almost non-conductive, with a resistance of 1 MΩ, while the resistance of the vermiculite nanosheet composite film in the embodiment is reduced to 12000Ω.
[0065] The above films were subjected to stability tests.
[0066] The vermiculite nanosheet composite film in the embodiment has extremely high stability. After being used for 60 days under normal temperature and pressure, its structure and function can remain normal.
[0067] After 60 days of storage, the water vapor ion exchange rate test was conducted again. Under the set experimental conditions of 30°C and 30% humidity, the residual water content of the experimental group (vermiculite nanosheet composite film in the embodiment) was 104.5 mL, and the residual water content of comparative example 1 was 186.4 mL. The water evaporation rate of the vermiculite nanosheet composite film was slightly improved, while the water vapor permeability of ordinary films such as PVC film was deteriorated.
[0068] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A vermiculite nanosheet composite film, characterized in that: The film comprises a functional layer (1) and a composite layer (2), wherein the functional layer (1) comprises vermiculite nanosheets, carbon nanotubes and rare earth metal oxide nanoslurry, and the composite layer (2) comprises a polymer electrolyte, a polyhydroxy organic acid and a water-absorbing inorganic salt; The carbon nanotubes are selected from one or more of hydroxylated carbon nanotubes and plasma surface treated carbon nanotubes, and the rare earth metal in the rare earth metal oxide nano slurry is selected from one or more of cerium, neodymium, thorium, yttrium and lanthanum; The polyhydroxy organic acid is selected from one or more of phytic acid, tannic acid, and gallic acid, and the water-absorbing inorganic salt is selected from one or more of lithium chloride, magnesium chloride, and calcium chloride; Vermiculite nanosheets are used as the functional layer: Vermiculite nanosheets have good hydrophilicity and ionic conductivity, which effectively guide the migration of water vapor. At the same time, their stable structural characteristics also ensure the stability of the material. Carbon nanotubes and rare earth metal oxide nano-slurry are added to the vermiculite nanosheets to fill the microscopic gaps, increase stability, and reduce overall resistance. Polymer electrolyte is used as the composite layer: polymer electrolyte has good hygroscopicity and ion conductivity, and can effectively absorb water vapor in the environment; by adding polyhydroxy organic acids and water-absorbing inorganic salts, the speed of moisture absorption and release, as well as the speed of ion migration, are greatly increased.
2. The vermiculite nanosheet composite film according to claim 1, characterized in that: The polymer electrolyte is selected from one or more of polyvinyl alcohol, polydiallyldimethylammonium chloride, polyethylene, polyamide, and polystyrene sulfonic acid.
3. The vermiculite nanosheet composite film according to claim 1, characterized in that: The thickness ratio of the functional layer (1) to the composite layer (2) is (1-10):(2-30).
4. A method for preparing a vermiculite nanosheet composite film according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: S1, dispersing vermiculite in water to form a vermiculite nanosheet suspension, adding carbon nanotubes to the suspension and ultrasonicating, then adding rare earth metal oxide nanoslurry to the suspension to form a functional liquid, filtering the functional liquid and drying it to obtain a functional layer (1); S2. The polymer electrolyte and the polyhydroxy organic acid are dissolved in water to form solutions and then mixed. A water-absorbing inorganic salt is added to the mixed solution to form a composite liquid. The composite liquid is dropwise applied on the functional layer (1) and then dried to form a composite layer (2) on the functional layer (1), thereby obtaining a vermiculite nanosheet composite film.
5. The method for preparing a vermiculite nanosheet composite film according to claim 4, characterized in that: In step S1, the mass concentration of the vermiculite nanosheet suspension is 1-20 g / L, the mass fraction of carbon nanotubes relative to vermiculite is 0.1-5 wt %, the mass fraction of rare earth metal oxide nanoslurry relative to vermiculite is 0.3-10 wt %, and the volume / thickness ratio of the functional liquid to the functional layer is (1-3 mL):(1-10 μm).
6. The method for preparing a vermiculite nanosheet composite film according to claim 4, characterized in that: In step S1, the vermiculite dispersion temperature is 20-35°C, the ultrasonic frequency is 15-35 kHz, the output power is 500-2000 W, and the time is 8-16h / 10 g vermiculite; The temperature of carbon nanotube ultrasound is 20-35 °C, the frequency is 15-25 kHz, and the time is 1-3 h; The rare earth metal oxide nano-slurry is mixed at a temperature of 20-35°C, a stirring rate of 200-500 rpm, and a time of 20-60 min; The functional liquid is dried at a temperature of 30-80°C and for 3-5 hours.
7. The method for preparing a vermiculite nanosheet composite film according to claim 4, characterized in that: In step S2, the mass fraction of the polymer electrolyte solution is 10-30 wt%, the mass fraction of the polyhydroxy organic acid solution is 15-35 wt%, the volume ratio of the polyhydroxy organic acid solution to the polymer electrolyte solution is 1:(1-5), the mass fraction of the water-absorbing inorganic salt relative to the sum of the polymer electrolyte solution and the polyhydroxy organic acid solution is 2-10 wt%, and the volume / thickness ratio of the composite solution to the composite layer is (1-10 mL):(2-30 μm).
8. The method for preparing a vermiculite nanosheet composite film according to claim 4, characterized in that: In step S2, the polymer electrolyte is dissolved at a temperature of 60-120°C, a stirring rate of 400-800 rpm, and a time of 1-2 h; The temperature for dissolving the polyhydroxy organic acid is 20-35 °C, the stirring rate is 200-500 rpm, and the time is 20-60 min; The water-absorbing inorganic salt is mixed at a temperature of 20-35°C, a stirring rate of 200-500 rpm, and a time of 20-60 min; The composite liquid is dried at a temperature of 50-100 °C and a drying time of 2-3 h.
9. The method for preparing a vermiculite nanosheet composite film according to claim 4, characterized in that: The method for loading the film on a support comprises the following steps: Water is dripped onto the support, the film is covered on the support, and the loading is completed after the water evaporates.
Citation Information
Patent Citations
Gas-barrier moisture-permeable film containing sulfonated polyaromatic ether polymer as well as preparation method and application thereof
CN111716846A
Gas-barrier and moisture-permeable film as well as preparation method and application thereof
CN113637210A
Moisture power generation device based on vermiculite nanosheet film and preparation method thereof
CN117578911A
Carbon nanotube containing dispersions and conductive films
TW200815283A